2014
DOI: 10.1515/htmp-2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular Corrosion Susceptibility of Alloy 600 after Autogenous Tungsten Inert Gas and Laser Beam Welding using Electrochemical Technique

Abstract: Intergranular corrosion and intergranular stress corrosion cracking is influenced by precipitation of chromium carbides at grain boundaries and formation of chromium depletion regions. The present study focuses on understanding the carbide precipitation and subsequent sensitization in the weldments of Alloy 600 using two different welding techniques. The effect of heat input on microstructure and IGC susceptibility was measured using electrochemical reactivation test. The SEM studies were done to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The SEM figure of Ni600 with the finely polished sample surface revealed black phases on the GBs that were considered to be chromium carbides [29], as is shown in Figure 3. The presence of these carbides can lead to intergranular corrosion and stress corrosion cracking [30]. The formation of chromium carbides is influenced by precipitations at GBs and the formation of chromium depletion regions.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM figure of Ni600 with the finely polished sample surface revealed black phases on the GBs that were considered to be chromium carbides [29], as is shown in Figure 3. The presence of these carbides can lead to intergranular corrosion and stress corrosion cracking [30]. The formation of chromium carbides is influenced by precipitations at GBs and the formation of chromium depletion regions.…”
Section: Resultsmentioning
confidence: 99%
“…Lim et al [6] observed that the precipitation of Cr carbides occurred preferentially in high-energy zones at the grain boundaries. In his study, Abraham [7] corroborated that the mechanism of precipitation was principally due to the low solubility of C in the Ni matrix and the high thermodynamic affinity of Cr to form compounds of different stoichiometry with C. The formation of Cr-rich carbides in IN600 may reduce the solid solution strengthening mechanism and lead to a loss in the intergranular corrosion resistance (IGCR) of the alloy. Yoo et al [8] reported that the precipitation of chromium carbides, namely, Cr7C3 and Cr23C6, in IN600 occurred in the temperature range of 550-1050 °C, but it might also occur at lower temperatures after very long exposures during service.…”
Section: Introductionmentioning
confidence: 97%
“…Yoo et al [8] reported that the precipitation of chromium carbides, namely, Cr7C3 and Cr23C6, in IN600 occurred in the temperature range of 550-1050 °C, but it might also occur at lower temperatures after very long exposures during service. The behavior and microstructural characterization of IN600 welds have been studied using a variety of filler materials and welding processes [2,7,[9][10][11][12]. When alloys are welded, a variety of microstructural changes take place at the base material (BM), leaving a heat affected zone (HAZ) with different microstructural features at each side of the welded joint.…”
Section: Introductionmentioning
confidence: 99%